Knowledge, attitude and practices of students on sexually transmitted infections : an assessment - Bilbao, Renz Raphael G.; Esparar, Devean Dean I.; Ochavez, Amery Christine D.; Siwala, Hazel Anne N. (Manila : National University, 2023)
This study may include various factors related to college students and may also be conducted at different universities in rural or areas, to further analyze the knowledge, attitude and practices of college students in sexually transmitted infections.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary of Findings, Conclusions and Recommendation -- References.
Includes bibliographical references.